STUDY ON THE THERMAL CHARACTERISTICS OF HYBRID NANOFLUID - SELLADURAI, SANGGKAR (IRC, 2019)
The study on stability of nanofluids is of utmost importance in order to to fully utilize its potentials especially the enhanced thermodynamic properties of the nanofluids. This study focuses on achieving the stability of nanofluids by changing the ratio of hybrid nanoparticles which are Magnesium Oxide (MgO), Zinc Oxide (ZnO), Aluminium Oxide (Al2O3) and multiwall carbon nanotube (MWCNT) nanoparticles in thermal oil. Sedimentation studies on the nanofluid suspensions with different concentration of nanoparticles (0.25, 0.5, and 1 wt. %) and base fluid (thermal oil) are to be carried out to compare the stability of the nanofluid. However, the stability of nanoparticles in the fluid have been one of the main issues that researcher are concerning with. The instability of nanoparticle cause sedimentation due to agglomeration of nanoparticles. Therefore, enhancement of nanofluid stability has been the main focus to improve the effectiveness of nanofluid applications. In this study, thermal oil is used as the base fluid and Sorbitane Trioleate (Span 85) is used as surfactant. The result proven that the nanofluid are more effective than thermal oil. The structure of the nanoparticles were observed by using the FESEM techniques. The TGA analysis is carried out and found that the decomposition rate of nanofluids are slower compared to pure thermal oil. The DSC analysis have also been carried out and it shows that nanofluids has less specific heat compared to pure thermal oil.